1963
DOI: 10.1152/ajplegacy.1963.204.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Local vascular effects of hypokalemia, alkalosis, hypercalcemia, and hypomagnesemia

Abstract: Blood flowing through the vascular beds of the dog forelimb, kidney, and heart was transiently rendered hypokalemic (1.9 meq/ liter), alkalotic (pH 7.54), hypercalcemic (6.4 to 13.5 meq/ liter), hypomagnesemic (1.2 meq/liter), and hypocalcemic (3.0 meq/liter), singly and in various combinations, while observing resistance to flow and heart contractility. This was accomplished by holding flow rate constant while measuring the effects of rapid intra-arterial infusion of various artificial solutions upon perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1967
1967
1994
1994

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…No significant or consistent influences on glomerular filtration rate or renal plasma flow have been reported following administration of potassium salts in amounts of the same order of magnitude used in the present studies. On the other hand, potassium depletion has been reported to reduce GFR and RPF (25) and acute hypokalemia has been noted to increase renal resistance (26). However, much more drastic or prolonged potassium depletion than that applied in the present studies was required to produce these changes.…”
Section: Potassium Administration and Plasma Renin In Manmentioning
confidence: 51%
“…No significant or consistent influences on glomerular filtration rate or renal plasma flow have been reported following administration of potassium salts in amounts of the same order of magnitude used in the present studies. On the other hand, potassium depletion has been reported to reduce GFR and RPF (25) and acute hypokalemia has been noted to increase renal resistance (26). However, much more drastic or prolonged potassium depletion than that applied in the present studies was required to produce these changes.…”
Section: Potassium Administration and Plasma Renin In Manmentioning
confidence: 51%
“…The resulting decrease in sodium delivery to the macula densa might be expected to stimulate renin release (14). Finally, the increased renin release might be directly related to increased renal resistance during potassium depletion (15). However, this is unlikely to be the sole or major stimulus since during the first few days of depletion, renin is greatly elevated while renal blood flow is still almost unchanged (16).…”
Section: Discussionmentioning
confidence: 99%
“…Five female mongrel dogs, weighing [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Plasma renin activities were determined by a modification (8) of the method of Boucher, Veyrat, de Champlain, and Genest (9). This method measures renin indirectly by assaying the quantity of angiotensin generated during a 3 hr plasma incubation under standardized conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In Oklahoma, in 1963, 24 using a dilutional method, and in Michigan, in 1972, 25 using a miniature hemodialyzer interposed in the arterial supply, we showed that local hypokalemia produces vasoconstriction in peripheral vascular beds, just the opposite of the vasodilation we observed in the dog forelimb with local hyperkalemia in 1959. 21 In 1966, Overbeck reported that this potassium vasodilation in the dog forelimb appears to be reduced in dogs with onekidney, one wrapped hypertension, a form of low renin hypertension.…”
Section: Ionic Action On Blood Vesselsmentioning
confidence: 66%